Restruksi* Estetika dalam Wujud Kosakarya Seni - Toekio, Soegeng (KEMADHA, 2011)
When people looked at clouds of dark clouds, people will assume that the rain will soon arrive; cloudy become markers hujan. Like markers that deliver meaning and we agree on the truth. In the scope of visual arts, certainly  not  that  simple  to  get  the  meaning  of  a  perupaan.  Various backgrounds on the following concepts of media used to be a differentiator . Kekaryaan or even the perpetrators are often targeted for a review and make conversation material. There was dialogue about  the work & perupanya, about the work and its economic impact, and so on. Unfortunately, however , is there any dialogue  to dissect  karyarupa  tradition  for  entries art of  science? Yes maybe one or  two of  limited community can only be done, but  the portion  that  is oriented  towards more macro may need  to be our concern.In  the atmosphere created by dualism mainstream of  the developing nations, will require many wise minds to be able to form a renewal without any cultural conflict. Negative picture of the atmosphere that can only be a source of catastrophe  for  the existence of cultural assets  that no  longer have a place  to exist. However ,  it does not mean  that  the old habits  that rests on peradatan was then  terluluhkan. Actually  there  are  superior  power  of  indigenous  culture (ethnicity) and has a  strong desire  to  keep  strong  in  the midst of a global culture. Excellence that has been proven true history has shown its reputation and acknowledged able to appear in the middle of chess world. Some are even no longer something that is familiar , such as: woven, batik, wayang, gamelan, keris  /  tosanaji,  weaving,  grabah,  and  other  kria  products  using  natural ingredients.Exposure will be delivered  is actually  trying  to  look  fragments of artistic assets are spread widely  in  the country  ini.Saya believe  there are enough young researchers who explored  it and make a  review about  it. However , what  is produced is still not supported by preaching and caring for the other party can strengthen  its contribution  to  the  science of our art.